2012
DOI: 10.3892/mmr.2012.1015
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin alleviates non-alcoholic fatty liver disease in rats by inhibiting the expression of TNF-α and SREBP-1c

Abstract: Abstract. The pathophysiology of non-alcoholic fatty liver disease remains incompletely elucidated, and available treatments are not entirely satisfactory. Polydatin, a stilbenoid compound derived from the rhizome of Polygonum cuspidatum, has been recognised to possess hepatoprotective and anti-inflammatory activities. The purpose of the present study was to determine whether polydatin has a protective effect against hepatic steatosis induced by a high-fat diet (HFD) and to elucidate its underlying molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…16 Similar to its analog resveratrol, polydatin has multiple pharmacological effects, including anti-inflammatory, neuroprotective, lipid-lowering actions, and especially strong antioxidative effects. [17][18][19] Recently, it was suggested that polydatin has strong protective effects against cardiac ischemia-reperfusion injury and pressure-overload-induced ventricular remodeling. [20][21][22][23] There are also studies showing that polydatin ameliorates burn-generated cardiac dysfunction by reducing oxidative modification of ryanodine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…16 Similar to its analog resveratrol, polydatin has multiple pharmacological effects, including anti-inflammatory, neuroprotective, lipid-lowering actions, and especially strong antioxidative effects. [17][18][19] Recently, it was suggested that polydatin has strong protective effects against cardiac ischemia-reperfusion injury and pressure-overload-induced ventricular remodeling. [20][21][22][23] There are also studies showing that polydatin ameliorates burn-generated cardiac dysfunction by reducing oxidative modification of ryanodine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the levels of TNF-a, MDA and 4-hexanonenal are markedly suppressed by PD in the liver of HFD-fed rats. PD also decreases the gene expression of sterol-regulatory element binding protein and its target genes involved in lipogenesis, including fatty acid synthase and stearoyl-CoA desaturase 1 in HFD-fed rats (Zhang et al, 2012b). Another in vivo test reveals that PD obviously reduces serum fasting insulin, fasting blood glucose, insulin resistance index and TNF-a level, and improves the insulin sensitivity index level, whose effects at high dose are better than those of fenofibrate (Zhang & Lv, 2010).…”
Section: Hepatoprotective Effectsmentioning
confidence: 99%
“…For example, chlorogenic acid could prevent fatty liver by upregulating the expression of peroxisomal proliferator‐activated receptor α (PPARα) (Alqarni, Bassiouni, Badr, & Ali, ; Wan et al, ). Geniposide and polydatin could alleviate high‐fat‐diet‐induced hepatic steatosis in rats, especially because geniposide exhibits antioxidant actions and could regulate the adipocytokine release and expression of PPARα (Ma et al, ), whereas polydatin could reduce liver tumor necrosis factor‐α (TNF‐α) expression, lipid peroxidation level, and sterol regulatory element‐binding protein‐1c (SREBP‐1c)‐mediated lipogenesis (Zhang, Tan, Yao, & Zhang, ). Resveratrol was proved to reverse the hepatic triglyceride content in high‐fructose‐corn‐syrup‐induced insulin resistance in rats by improving insulin signaling and suppressing the expression levels of SREBP‐1c in liver (Sadi et al, ).…”
Section: Resultsmentioning
confidence: 99%